2013
DOI: 10.2174/1876823701305010005
|View full text |Cite
|
Sign up to set email alerts
|

Association of Depressive Symptoms and Anti-Depressants with Body Mass Index and Waist Circumference in Elderly Men and Women: The ARIC Carotid MRI Study

Abstract: Abstract:Background: Depressive symptoms are associated with obesity, a precursor to type 2 diabetes and cardiovascular disease, and might in part explain the association of depressive symptoms with adverse metabolic outcomes. We determined the cross-sectional association between depressive symptoms and body mass index (BMI) and waist circumference (WC) in 1,314 elderly men and women age 60 to 83 years in the Atherosclerosis Risk in Communities (ARIC) Carotid MRI Study.Methods: Depressive symptoms were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…The results are similar to those of previous studies which suggested that depressive symptoms are associated with reduced physical activity [ 28 , 29 ], smoking [ 30 – 32 ], high BMI [ 33 , 34 ], and increased weight [ 35 , 36 ]. However, these studies often recruited patients with either new onset depression which occurred after a heart event or general population without CVD.…”
Section: Discussionsupporting
confidence: 91%
“…The results are similar to those of previous studies which suggested that depressive symptoms are associated with reduced physical activity [ 28 , 29 ], smoking [ 30 – 32 ], high BMI [ 33 , 34 ], and increased weight [ 35 , 36 ]. However, these studies often recruited patients with either new onset depression which occurred after a heart event or general population without CVD.…”
Section: Discussionsupporting
confidence: 91%